The Role Of Oceanic Plateau Volcanism On Climate Change: Warming And Cooling Episodes Across Early Aptian Oceanic Anoxic Event 1a - C. Bottini; E. Erba; J. Mutterlose (2011)
The early Aptian is marked by a global phenomenon of organic matter burial in oxygen-depleted oceans known as Oceanic Anoxic Event 1a (OAE 1a: ~120 Ma). Volcanism associated with the emplacement of the Ontong Java Plateau (OJP) is thought to be the main triggering mechanism for global anoxia, ocean acidification and greenhouse conditions. However, climate instability during OAE 1a is indicated by independent studies on TEX86, sporomorphs and oxygen-stable isotope but a direct connection between OJP volcanic phases and temperature variations has not been ascertained. A high-resolution integrated nannofossil-geochemical investigation of distant sections from the Tethys, the Pacific Ocean and the Boreal Realm has revealed systematic and synchronous changes. Specifically, the nannofossil Temperature Index and Os-isotope records allowed the reconstruction of a complex series of global warming and cooling events across OAE 1a and their relationships with OJP volcanism as well as weathering patterns. Two prominent volcanic phases are documented in the Os-isotope records: the first preceding OAE 1a and the second one, of major intensity, starting in the core of the negative C-isotopic anomaly. Both phases are paralleled by increased temperature, suggestive of a (super)greenhouse climate triggered by excess volcanogenic CO2. Indeed, our data indicate that the beginning of the prolonged volcanic phase during OAE 1a coincides with warmest temperatures. In the early part of OAE 1a, between the two major volcanic phases, there is a ~100 kyrs-long interval characterized by a radiogenic Os-isotope peak, suggestive of accelerated continental weathering rates, with or without volcanism cessation, following an interval of abrupt warming and preceding a cooling interlude. Arguably, warming at OAE 1a onset promoted methane hydrate dissociation (also suggested by C-isotope and biomarkers analyses), which was perhaps instrumental in triggering continental weathering. Subsequent CO2 draw down, possibly during OJP quiescence, might ...